PENERAPAN SISTEM PAKAR MENDIAGNOSA KARAKTERISTIK PENYALAHGUNAAN NARKOBA BERBASIS WEB - Arwin, elfani; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2023)
Narkoba is an abbreviation for narcotics, psychotropics, and other addictive materials. Drugs themselves can be interpreted as artificial substances that affect the behavior, thoughts, feelings, and conditions of the consumer. Drugs or narcotics can also be interpreted as natural, semi-synthetic, or synthetic substances or drugs that can cause decreased consciousness, excitability, and hallucinations. These drugs cause addiction due to excessive use. The reason for using forward chaining is that many different methods and rules for drawing conclusions are very simple, and researchers want to draw conclusions from the truth. To overcome this problem, researchers use the forward chaining method, which allows them to find solutions based on symptom data selected by the user. The system built can provide suggestions in the form of diagnostic results and solutions based on the facts presented.